Presença de Tomás de Aquino na concepção de pessoa na Antropologia de H. C. de Lima Vaz - Silva, Laureandro Lima da (2022)
The thesis Presence of Thomas Aquinas in the conception of person in the Anthropology of H.C. de Lima Vaz aims to analyze the specific problem of Aquinate's relationship in the development of the conception of man within the Anthropology of the Brazilian author. Thomas Aquinas is the author's guide to conceiving metaphysical ideas about human life and the great dimensions that integrate the person and their relationships. In addition, it helps Vaz affirm the dimension of Transcendence and consider the horizon of soteriological hope, serving as support for updating the concept of the human person in contemporary culture. The subject was organized into three planes. Firstly, Thomas Aquinas’s references in H. C. de Lima Vaz will be presented, bringing to light the presence of Aquinate in the Brazilian author's project of reconstruction of the genesis, nature, and destiny of modernity. The themes of the human being rescued in publications on Thomas Aquinas and the work of Philosophical Anthropology will be addressed, highlighting the classical and Christian-medieval conceptions of man. The second moment deals with the concept of person in Thomas Aquinas's Summa Theologica, presenting the notes on the main references, and emphasizing question 29. The three coordinates of Thomistic anthropology are discussed: individual substance person of rational nature, human person composed of soul and body, and the human person created in the image and likeness of God. The third plan tries to prove the conception of person in the philosophical Anthropology of H. C. de Lima Vaz under the inspiration of Thomas Aquinas, understanding the person as a synthesis between essence and existence: the structures and relationships of the person. And presenting the person as a being suited to life according to the spirit: spiritual acts and spiritual intelligence, the category of person, and the problem of the person between time and eternity